Magpie learns a lesson - Morgan, Sally, 1951 January 18-; Erzinger, Tania; Kwaymullina, Ezekiel (Gosford, NSW : Scholastic Australia Pty Ltd, 2015)
Magpie is cross that she can't fly like her friend Brown Falcon. She thinks of mean tricks that will make Brown Falcon look silly. But she goes too far ... and finds out just how much friends need each other.
For pre-school age.
Keywords: Friendship -- Pictorial works -- Juvenile fiction; Magpies -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; Australian